International Master Program as a Resource for Internationalization of Educational Environment - I. Yu. Malkova; O. G. Maslennikova (Высшее образование в России, 2018)
At present, all the spheres of life of the world society are under the influence of constant, continuous and intensive changes such as digitalization, automation of various types of human activities, as well as changing of value orientations, which requires a revision of the basic competencies of modern specialists able to work effectively in the conditions of the global market. In education there is a gap between the expectations of employers and the real competencies of graduates, between the dissatisfaction of graduates with the knowledge and skills acquired at the factory and the willingness of universities to respond to employers and students’ requests for the formation of competencies necessary for graduates. This article considers the issues connected with formation of a model of internationalization of educational environment of the Russian universities at the graduate level as well as the processes of the transformation of educational model. The characteristics of a modern global graduate who is able to live and work in the multicultural and multilingual society are considered in the article. An analysis of the national experience of graduate training in Russian research universities showed that now there is a lack of systematic and conscious use of the mechanisms of internationalization; as well as a deficit of scientific and pedagogical staff who are able to use and teach the students global competencies.